Determination of car run up – braking and manoeuvring parameters in an emergency situation in the case of limited road segment - Lukoševičiene, Ona; Pečeliūnas, Robertas (Transport, 2005)
As the traffic intensity on roads increases, the number of road accidents also increases and the situations become more and more complicated. The presented method of reconstruction of preaccidental situations with the purpose of examination of road accident mechanisms can be widely used for the investigation of road accidents of different nature and for the determination of their reasons, the distance run by a car, the time of its run and speed which can be reached during the run up and followed by braking in road segments between two manoeuvres in a road segment of limited length. This method is being widely used in Lithuania for the investigation of accidental situations and for the assurance of law and order. First Published Online: 27 Oct 2010